Refugee camps reconsidered - Jeff Crisp (Forced Migration Review, 1998)
In this issue we present an article by Jeff Crisp and Karen Jacobsen, submitted in response to the feature section on ‘people in camps’ in FMR 2, plus a reply by Richard Black, author of the introductory article ofthe ‘people in camps’ feature.